SUBFRACTIONAL SPECTRUM OF HIGH DENSITY LIPOPROTEIDS IN CORONARY ATHEROSCLEROSIS PATIENTS - I. N. Ozerova; V. A. Metelskaya; N. V. Perova; N. E. Gavrilova; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 2015)
Aim. To analyze a dispersion of high density lipoproteid (HDL) particles in patients with coronary atherosclerosis and to find out whether there is a relation of HDL subfractional specifics and severity of coronary lesion. Material and methods. Totally 130 patients included (M/F 84/46) 30-80 y.o. (mean age 61, 1 ±9,9 y.o.), who underwent coronary arteriography. Subfractional spectrum of HDL was assessed by "Lipoprint System" (Quantimetrix Lipoprint System, US). Results. Patients were selected into 3 groups according to Gensini score: 1 group (n=40) — coronary lesion 0-20% — no clinical signs of coronary heart disease (0 points); 2 group (n=40) — moderate lesion 21-70% (1-34 points); 3 group (n=50) — significant lesion (>35 points; 35-176). Patients of the 2 and 3 groups comparing to those without coronary atherosclerosis (1 group) had lower levels of cholesterol (C); C of low density lipoproteids (LDL), apoliporotein (apo) AI and apo B, and the level of HDL-C and triglycerides, carbohydrate metabolism parameters (glucose level, insulin and insulin resistance index) and hi- sensitivity C-reactive protein did not differ in three groups, and had higher portion of smaller dense HDL and intermediate HDL, and less amount of large HDL. The differences in HDL dispersion among 2 and 3 groups patients were not found.Conclusion. A pattern of HDL dispersion, i.e. the higher relative amount of smaller dense particles of HDL and less amount of larger HDL is associated with coronary arteries lesion. Shift in subfractional spectrum of HDL to the side of potentially proatherogenic HDL particles can be found in patients even at earlier stages of atherosclerosis.